Consumer Interpretation of Trust in Shopee Reviews and Ratings: A Warranting Theory Perspective - Dewi Ika Wijayanti; Prita Suci Nurcandrani; Adinna Islah Perwita (Universitas Multimedia Nusantara, 2025)
The development of e-commerce has changed people's consumption patterns in shopping, including in the purchasing decision-making process, which is now increasingly considered through online consumer reviews and ratings. This study aims to understand how consumers assess warranting cues and warrant value in reviews and ratings of local fashion products from the Erigo and Executive brands on Shopee. The main theory used Warranting Theory which explains that information from third parties is more credible than information from the seller. This study was conducted using a descriptive qualitative approach. Data collection techniques used observation, in-depth interviews, and documentation, while the selection of informants used purposive sampling. The results show that consumers assess trust based on the presence of Warranting Cues, such as visual evidence in the form of photos or videos, detailed product reviews based on personal experience, a minimum rating of four stars, and a high number of review likes. The identity of the review author is also an important consideration. In addition, the Shopee Mall label and brand image play a supporting role in building a stronger Warranting Value, so that reviews are considered more credible and convincing to be used as a basis for consideration in purchasing a product.